2010
DOI: 10.1172/jci36714c1
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid mediates hypothalamic insulin resistance by altering PKC-θ subcellular localization in rodents

Abstract: During the preparation of the manuscript, the number of samples used for the quantification of RT-PCR depicted in Figure 2E was stated incorrectly. The corrected legend appears below.(E) mRNA expression of TRPA1 and TRPM8 in the DRG after inflammation, as detected by RT-PCR. Quantification of RT-PCR data is shown at right. Data represent mean ± SD; n = 3 per group. *P < 0.05 compared with the naive control.The authors regret the error. During the preparation of the manuscript, the vehicle for ICV fatty acid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
102
1
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(125 citation statements)
references
References 0 publications
12
102
1
10
Order By: Relevance
“…At that time, we speculated that fatty acids derived from visceral fat depots may cause insulin resistance of the brain and therefore lead to further weight gain. Indeed, recent studies confirmed that intracerebroventricular palmitic acid infusion and high-fat diet induce insulin resistance in different brain regions in mice and rats [12,14,15]. These observations, together with the present finding of high insulin sensitivity in the brain associated with lower intake of saturated fat, may suggest that insulin resistance in the brain elevates serum concentrations of saturated fatty acids not only by increasing visceral fat mass, but also more directly by decreasing physical activity and increasing intake of saturated fat.…”
Section: Discussionsupporting
confidence: 83%
“…At that time, we speculated that fatty acids derived from visceral fat depots may cause insulin resistance of the brain and therefore lead to further weight gain. Indeed, recent studies confirmed that intracerebroventricular palmitic acid infusion and high-fat diet induce insulin resistance in different brain regions in mice and rats [12,14,15]. These observations, together with the present finding of high insulin sensitivity in the brain associated with lower intake of saturated fat, may suggest that insulin resistance in the brain elevates serum concentrations of saturated fatty acids not only by increasing visceral fat mass, but also more directly by decreasing physical activity and increasing intake of saturated fat.…”
Section: Discussionsupporting
confidence: 83%
“…It is also expressed in natural killer cells 39 ; in platelets, where it may modulate activation and thrombus formation 40 ; in skeletal muscle cells 41 ; in the endothelium of muscle resistance arteries, where it modulates vascular tone through insulin-induced vasoconstriction 42 ; and in hypothalamus tissue, where it contributes to insulin signaling. 43 PKC-could, therefore, exert multifold influence on development of CM, through platelet activation and vascular tone modulation, beyond a direct effect on T cells.…”
Section: Discussionmentioning
confidence: 99%
“…L'administration intrahypothalamique de C75, un inhibiteur de FAS, qui induit également une augmentation de la concentration en acyl-CoA, diminue la prise alimentaire et induit une baisse du poids corporel [28]. [36]. Lorsqu'on perfuse in vivo du palmitate par voie intracérébroventriculaire chez le rat, on provoque un ancrage de la PKC  dans la membrane plasmique, ce qui a pour conséquence de l'activer et, consécutivement, de perturber la voie de signalisation hypothalamique de l'insuline [36].…”
Section: Effets Des Acides Gras Sur Le Contrôle Nerveux De La Balanceunclassified
“…[36]. Lorsqu'on perfuse in vivo du palmitate par voie intracérébroventriculaire chez le rat, on provoque un ancrage de la PKC  dans la membrane plasmique, ce qui a pour conséquence de l'activer et, consécutivement, de perturber la voie de signalisation hypothalamique de l'insuline [36]. On induit ainsi une résistance hypothalamique et, en conséquence, l'apparition d'une résistance à l'insuline hépatique, démontrant que l'apport excessif de lipides au niveau central perturbe le contrôle nerveux de la production hépatique de glucose, rendant l'insuline moins efficace.…”
Section: Effets Des Acides Gras Sur Le Contrôle Nerveux De La Balanceunclassified
See 1 more Smart Citation